Parâmetros cinéticos da cristalização de sacarose em diferentes escalas - Barros, Guilherme López (2018)
This work aims to determine kinetic parameters capable of describing the crystallization of sucrose using bench scale and pilot scale reactors. Sucrose was chosen because it is a very important product for Brazil, which is responsible for exporting 50% of the world's import demand, being the biggest producer and exporter of sucrose in the world. In order to obtain the necessary parameters to optimize existing equipment and to enable the design of new ones, 15 experiments were carried out in a reactor with a volume of 1 liter, the bench scale reactor, and 5 experiments in a reactor a volume of 10 liter, identified as the pilot scale reactor. In the bench reactor the turbidity of the suspension was monitored, which can be related to the crystal surface area, and in 12 out of 15 experiments were varied the stirring velocity, the cooling rate and the initial sucrose concentration, 60, 70 and 80 rpm, 0.106 ⁰C/min and 0.760 ⁰C/min and 3.7 and 2.9 gsucrose/gwater, and the solution was seeded 2 ⁰C below the saturation temperature. In the other three experiments the stirring speed was set at 70 rpm, the cooling rate was set at 0.185 ⁰C/min and the initial sucrose concentration was sat at 2.9 gssucrose/gwater and the solutions were seeded at 4, 9 and 14 ⁰C below the saturation temperature. The experimental results of the cooling crystallizations in the bench scale reactor and the pilot reactor obtained and the adjusted kinetic parameters are presented and discussed. It is concluded that agglomeration occurs intensely during the crystallization of the sucrose, surpassing the secondary nucleation and that the experiments with a stirring speed set at 70 rpm in the bench reactor were the most affected. The temperature significantly affects the kinetics of crystallization and the estimated mean nucleation and growth parameters apply at both scales. A general adjustment was made with all the experiments that presented a good potential, since it was adjusted taking into account the speed at the tip of the impeller, thus being able to have the parameters adapted for different scales or operating conditions.